2020
DOI: 10.1097/brs.0000000000003706
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of Flexion-extension Central Motor Conduction Time in Cervical Spondylotic Myelopathy

Abstract: Study Design. Retrospective study Objective. The purpose of this study was to assess the diagnostic usefulness of flexion-extension central motor conduction time (CMCT) for patients with cervical spondylotic myelopathy (CSM). Summary of Background Data. Previous reports have suggested that cervical cord compression can be aggravated by neck motions. Thus, the importance of dynamic magnetic resonance imaging (MRI) has been emphasized. However, authors of this study found no reports conducted at the time of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Yoshimatsu et al's (30) multivariable logistic regression model showed that the patient's disease duration, one of the top-five important variables for both our models, should primarily be considered when deciding conservative treatment for DCM. Meanwhile, it was reported that CMCT correlated with the degree of spinal cord compression reported in imaging findings (31,32). CMCT has been known as one of the essential diagnostic tools in myelopathy because it reflects mechanical compression as well as the functional integrity of the motor pathway (33).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshimatsu et al's (30) multivariable logistic regression model showed that the patient's disease duration, one of the top-five important variables for both our models, should primarily be considered when deciding conservative treatment for DCM. Meanwhile, it was reported that CMCT correlated with the degree of spinal cord compression reported in imaging findings (31,32). CMCT has been known as one of the essential diagnostic tools in myelopathy because it reflects mechanical compression as well as the functional integrity of the motor pathway (33).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluating patients with cervical myelopathy using CMCT included ,100 patients, with the largest sample size being 223 patients. [8][9][10][11][12][13][14][15] Previous studies evaluating patients with thoracic myelopathy using CMCT had a sample size of 4-20. 5,[16][17][18] Accordingly, the present study included a relatively larger sample size than previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Right-Left differences of the same patients’ MEP or SEP parameters are also crucial in detecting abnormalities. DCM patients’ CMCT prolonged significantly at cervical extension or flexion positions compared with that at neutral, and thus the dynamic MEPs could also be used to increase the diagnostic sensitivity ( Park et al, 2020 ). We also developed dynamic SEPs to achieve higher diagnostic sensitivity and specificity for DCM than ordinary SEPs or MEPs ( Qi et al, 2020 ; Yu et al, 2020 ).…”
Section: Electrophysiology Tests For Dcm Diagnosismentioning
confidence: 99%
“…HD and CSA are two kinds of disease characterized with weakness and wasting of upper limb muscles. In HD, dynamic neurophysiological tests show a reversible significant prolonged CMCT in MEP and decreased SEP N13 amplitude and prolonged N13–N20 interval only upon neck flexion ( Restuccia et al, 2003 ; Zheng et al, 2017 ; Park et al, 2019 ), whereas DCM patients show MEP and SEP deterioration at both extension and flexion ( Park et al, 2020 ; Qi et al, 2020 ; Yu et al, 2020 ). Furthermore, Preethish-Kumar et al (2016) used EMG to reveal grossly reduced CMAP amplitudes of affected muscles in HD patients.…”
Section: Electrophysiology Tests For Dcm Diagnosismentioning
confidence: 99%